WOMEN IN THE SHADOW OF TERRORISM: EXPOSING THE DISCURSIVE AWARENESS BEHIND THE DIVORCE OF TERRORIST WIVES IN INDONESIA - Ari Alfiatul Rochmah; Alanuari Alanuari (Jurnal Sosiologi Reflektif, 2023)
In 2022, the National Counter-Terrorism Agency released data that over the last 10 (ten) years the involvement of women in terrorism activism has increased by 10%. The increase was coupled with an increase in divorce cases among spouses of perpetrators of terrorism. The objective of this study is to elucidate the reasons and mechanisms behind the correlation between the surge in women's involvement in terrorism and the phenomenon of divorce. The data were collected through in-depth interviews, observations, and tracing of data from the National Counter-Terrorism Agency. The data collected were then analyzed using Anthony Giddens' Structural Theory. According to the findings, multiple factors contributed to the divorce of terrorist couples, such as insufficient financial resources, pressure from peer groups to end the marriage due to differences in supporting the Islamic State, and the realization of no longer wanting to be associated with husbands engaged in terrorist activities. By applying Giddens' framework, these results formed a compelling argument that the wives of terrorists possessed a discursive awareness of the societal context in which they lived, leading them to make the decision to divorce their husbands.Tahun 2022, BNPT merilis data bahwa selama 10 (sepuluh) tahun terakhir pelibatan perempuan dalam aktivisme terorisme telah meningkat 10%. Peningkatan tersebut telah diiringi dengan peningkatan kasus perceraian di kalangan pasangan suami-istri pelaku terror. Penelitian ini bermaksud untuk menjelaskan mengapa dan bagaimana fenomena perceraian tersebut menggejala seiring dengan peningkatan pelibatan perempuan dalam terorisme. Data dikumpulkan melalui wawancara mendalam, observasi, dan penelusuran data BNPT. Data yang terkumpul selanjutnya dianalisis dengan menggunakan Teori Strukturasi dari Anthony Giddens. Hasil penelitian menunjukkan bahwa terdapat beberapa factor yang menyebabkan perceraian di kalangan pasangan teroris, diantaranya: faktor ketidakterpenuhinya kebutuhan ekonomi, dorongan peer-group untuk bercerai karena sudah tidak sepemahaman dalam menegakkan Daulah Islamiyah, dan adanya kesadaran untuk tidak lagi terikat dengan suami yang terlibat terorisme. Melalui Strukturasi Giddens, temuan ini kemudian menjadi argumen kuat bahwa istri teroris memiliki kesadaran diskursif akan realitas sosial yang mengelilinginya, dan kemudian mendorongnya untuk memutuskan bercerai dengan suaminya.